SPIRITUAL QUOTIENT DALAM PENGEMBANGAN PENDIDIKAN ISLAM MULTIKULTURAL DI SMA NURUL HIDAYAH - Qomariyah, Nurul; Wahyuni, S. (Tamaddun : Jurnal Pendidikan dan Pemikiran Keagamaan, 2024)
Spiritual intelligence is very much needed in human life. Because spirituality can be used to stem our bad behavior to become better. Spiritual intelligence is soul intelligence that helps a person to develop himself as a whole through creating the possibility to apply positive values. There is more value for every human being in developing their mindset so that they are able to develop and think clearly to consider, decide and face things by focusing on the problems they face and brilliant solutions. This reality can be seen from the dynamics of diverse people's lives, both in terms of religion, ethnicity, language and culture. The existing diversity can actually be a great potential for the nation's progress. However, on the other hand, it also has the potential to cause various kinds of problems if it is not managed and developed properly. This research uses a descriptive qualitative approach. Data collection uses observation, interviews and documentation. The important thing that is needed is to design some educational curriculum material content for students so that they can accept other people as equals and respect their religion, culture and ethnic differences. Therefore, a curriculum model with a variety of themes is a curriculum model that is highly recommended.